Public Understanding of Adolescents' Risks on Facebook in Taiwan - Yue Tan (MDPI AG, 2022)
An increasing number of parents and scholars have begun expecting schools and the government to share the responsibility of reducing the potential negative effects of SNS use among adolescents. This study examines how the public understands the risks that adolescents face, as well as the causes and solutions, and how news media influence not only the public's risk perceptions but also their policy preference for public interventions. Drawing on framing and attribution theories, this study used two datasets. First, the content analysis data explore Taiwanese news media's coverage of youths' online behaviors and how the media has framed the question "Who is responsible for adolescents' risky and opportunity behaviors?" Second, the public opinion survey data addresses the influence of news consumption on the public perception of the risks facing adolescent Facebook users, the public's attribution of related responsibilities to various stakeholders, and the public's evaluation of parental mediation and government regulations.